Proses Upgrade Komunikasi Distributed Control System dari Remote Input/Output ke Network Input/Output - Fitria Hidayanti; Fitri Rahmah; Dimas Sigit Priyatna; Ardiyanti Aulia (Universitas Indraprasta PGRI Jakarta, 2022)
The use of control systems for industrial automation is currently achieving rapid movements, one of which is the Distributed Control System (DCS). DCS has several generations in terms of software and hardware. This research discusses DCS upgrades in terms of hardware. Upgrading DCS from Remote Input/Output (R I/O) to Network Input/Output (N I/O) has two stages, upgrade software and hardware upgrading run simultaneously. CS 3000 is still integrated with Windows 7, which is software from R I/O, while to keep up with the development of Windows technology, 10 R I/O cannot reach it. For N I/O itself, it uses Centum VP software that is integrated with Windows 10. R I/O is limited to using RJ45 cable, which has a range of tens of meters, so it must use a repeater to connect long-distance communication. While, in communication between Marshalling Cabinets with field instruments, fibre optics can reach 5 km, save costs, transfer data faster, and only need one connecting cable.